Seizure-Related Homolog Protein 6 (SEZ6) : Biology and Therapeutic Target in Neuroendocrine Carcinomas - Gezelius, Emelie; Rekhtman, Natasha; Baine, Marina K.; Rudin, Charles M.; Drilon, Alexander; Cooper, Alissa J. (Clinical Cancer Research, 2025)
Seizure-related homolog protein 6 (SEZ6) is a cell surface type 1 transmembrane protein involved in neuronal development, the expression of which in adult tissues is almost exclusively limited to the central nervous system. Aberrant expression of SEZ6 has been associated with neurodevelopmental and psychiatric disorders including epilepsy, schizophrenia, and Alzheimer disease. More recently, SEZ6 overexpression has been detected in small cell lung cancer (SCLC) and other high-grade neuroendocrine malignancies, although our understanding of the function of SEZ6 as a driver of cancer is limited. A lineage-defining transcription factor of SCLC, ASCL1, has been implicated as a regulator of SEZ6 expression. SEZ6 has emerged as a novel target for antibody–drug conjugate therapy, and early studies have shown promising antitumor activity, demonstrating the potential for SEZ6 to be targeted by drugs with alternate mechanisms of action. In this article, we review the current knowledge of the biology of SEZ6 and its implications in malignancy, summarize the preclinical and clinical findings of SEZ6-targeted antibody–drug conjugates, and discuss future directions to further elucidate the role of SEZ6 in SCLC and other neuroendocrine neoplasms.
Publisher Copyright: © 2025 American Association for Cancer Research.